2017
DOI: 10.1080/03630242.2017.1282398
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and disordered eating: A qualitative study

Abstract: Quantitative studies have demonstrated a positive association between trauma exposure and disordered eating. However, reasons for this relationship are unclear. We used qualitative methods to understand why some individuals exposed to trauma report disordered eating. We conducted five focus groups and two dyadic interviews between spring 2013 and fall 2014 with women at a Veterans Health Administration medical center (N = 20). Most participants were recruited from outpatient mental health clinics. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Our findings are supported by past work identifying specific pathways from sexual trauma to disordered eating (e.g., disordered eating as way to change shape and weight to avoid attention from trauma perpetrators (Breland et al, 2017; Mott et al, 2012)). It is less clear why combat exposure was not associated with eating disorders.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings are supported by past work identifying specific pathways from sexual trauma to disordered eating (e.g., disordered eating as way to change shape and weight to avoid attention from trauma perpetrators (Breland et al, 2017; Mott et al, 2012)). It is less clear why combat exposure was not associated with eating disorders.…”
Section: Discussionsupporting
confidence: 87%
“…We used a logistic regression model to predict whether participants met criteria for an eating disorder as a function of military sexual trauma and combat exposure. While anorexia, bulimia, and binge eating disorder can have different courses and treatment, we included them as a single outcome variable due to past work demonstrating that women may restrict or binge as a result of traumatic exposures (Breland et al, 2017). We adjusted analyses for participant characteristics that may be related to disordered eating (i.e., age, race, education, service branch (Bartlett & Mitchell, 2015; Gagne et al, 2012; Mitchison & Hay, 2014; Smolak, 2015)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others used disordered eating to cope with trauma-related negative affect (often in relation to military sexual trauma), either by using food to numb emotions, to increase positive affect, or to reduce negative affect (Breland, Donalson, Dinh, & Maguen, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that DE is generally defined as a psychological illness [ 2 ]. Exposure to traumatic events (TEs) may be a risk factor for subsequent development of DE [ 3 ], as it can provide short-term, but not long-term, relief from trauma-related negative effects [ 4 ]. Studies investigating patients with anorexia or bulimia nervosa found high prevalence of posttraumatic stress (PTS) symptoms among them [ 5 ].…”
Section: Introductionmentioning
confidence: 99%